2016
DOI: 10.1016/j.ijcha.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of no-reflow post primary percutaneous coronary intervention for ST elevation myocardial infarction

Abstract: BackgroundNo-reflow (TIMI < 3) during primary PCI (PCI) for STEMI occurs in 11–41% of cases, indicates poor myocardial tissue perfusion, and is associated with a poor outcome. We aimed to determine predictors and 12 month outcomes of patients who developed no-reflow.MethodsWe analysed the PCI database of The Canberra Hospital and identified 781 patients who underwent primary PCI during 2008–2012. Follow-up at 12 months was with letter, phone call and review of hospital records.ResultsNo-reflow was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 31 publications
7
39
0
4
Order By: Relevance
“…Significant longer reperfusion time in patients with noreflow was concordant to many studies [1,5,14] but discordant to others [11][12][13]15].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Significant longer reperfusion time in patients with noreflow was concordant to many studies [1,5,14] but discordant to others [11][12][13]15].…”
Section: Discussionsupporting
confidence: 86%
“…Myocardial blush grade was not used as most angiogram films were not acquired long enough to estimate the MBG and the TIMI flow grade classification system was used only to assess epicardial coronary blood flow. This was concordant to many studies [1,5,[11][12][13][14] but discordant to Chen who used TIMI flow grade system and MBG to define no-reflow [15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This effect is known as the no-reflow phenomenon. In a recent work published by Hassan et al, 2018, they reported a 30 % no-reflow in patients with PPCI in Assuit University [13] while Mazhar et al, 2016 [14] reported 25% no-reflow in their patients' group. In this study we chose to examine patients who experienced no-reflow as a case control study.…”
Section: Discussionmentioning
confidence: 96%
“…However, the pathophysiological explanations and clinical implications of this biphasic shape had not been fully established. MVO is independently correlated with poor outcome after STEMI [4,[27][28][29]. There are conflicting results regarding the predictive factors for MVO [3,4].…”
Section: Hs-tnt and Myocardial Infarction Characteristicsmentioning
confidence: 99%